Masa simpan tempe dalam pengemas edible film tapioka termodifikasi [Shelf life of tempe wrapped by modified-tapioca edible film] - Maria Erna Kustyawati; Dian Santoso Manalu; Murhadi Murhadi; Ahmad Sapta Zuidar; Diki Danar Tri Winanti (Jurnal Teknologi & Industri Hasil Pertanian, 2021)
Edible film made up of modified tapioca was used to wrap tempeh and its shelf life estimation was determined. The edible films must be capable of evenly aerating and maintaining moisture without causing condensation in order mycelium to be able to grow and produce high-quality tempeh. The experiment was carried out in completely randomized design with two main factors of storage temperature and time. An accelerated shelf life test at 17oC, 27oC, and 37oC with an Arrhenius model was used to calculate the shelf life, and water content was used as quality parameter indicator. The result showed that modified-tapioca based edible film made from fermentation of tapioca by Saccharomyces cerevisiae was characterized as having elongation of 11.40 %, tensile strength of 408.37 MPa, thickness of 0.88 mm and WVTR of 12.60 g/m2/h. Rate constant of water content decrease in edible film wrapped tempeh based on Arrhenius model was 0.3832 % day-1 and Ea was 10.296 kkal/gmol, while that of in PP-plastic wrapped tempeh was 0.3831% day-1 and Ea was 9.998 kkal/gmol. The shelf life of edible film wrapped tempeh was 9.39 days at 27oC, 5.18 days at 27oC, and 2.96 days at 37oC, while shelf life of PP-plastic wrapped tempeh was 8.64 days at 17oC, 4.85 days at 27 oC, and 2.82 days at 37oC. Therefore, it can be concluded that modified tapioca based edible film increased the shelf life of tempeh.